2003
DOI: 10.1002/hed.10235
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor C and vascular endothelial growth factor receptor 3 expression in squamous cell carcinomas of the head and neck

Abstract: The broad expression of VEGF C and VEGFR3 in HNSCC suggests involvement in tumor lymph angiogenesis and vascular angiogenesis, promoting tumor growth and propagation of cancer cells. This implies that inhibitors of lymph angiogenesis could become effective therapeutic options similar to classical angiogenesis inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
0
3

Year Published

2005
2005
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(74 citation statements)
references
References 36 publications
4
64
0
3
Order By: Relevance
“…Previous reports 25,26 demonstrated the existence of VEGF receptors in head and neck squamous cell carcinoma cells, along with a predominant overexpression of VEGFR-2. This is in agreement with our results.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Previous reports 25,26 demonstrated the existence of VEGF receptors in head and neck squamous cell carcinoma cells, along with a predominant overexpression of VEGFR-2. This is in agreement with our results.…”
Section: Discussionmentioning
confidence: 87%
“…Similar paracrine action between cancer cells and stromal cells that infiltrate the tumor was previously described. 26 Some limitations of our study should be discussed. First, the sample size is limited and does not allow the performance of multivariate analysis.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Among the angiogenic cytokines, VEGF-C draws special attention because of its potential involvement in the lymph node metastasis of several cancers includingcolorectal cancer, human pancreatic endocrine tumors, esophageal carcinomas, head and neck squamous cell carcinoma, uterine cervical cancer, primary non-smallcell lung cancer, gastric carcinoma, and laryngeal squamous carcinoma (Yonemura et al, 1999;Hashimoto et al, 2001;Kimura et al, 2003;Neuchrist et al, 2003;Jia et al, 2004;Sipos et al, 2004;Wang et al, 2004). Recently, Tsurusaki et al reported a significant correlation between the expression of VEGF-C and lymph node dissemination in human prostate carcinoma (Tsurusaki et al, 1999).…”
Section: Introductionmentioning
confidence: 99%